SWOT ANALYSIS OF HUMAN RESOURCE MANAGEMENT IN CULINARY SME IN MOJOKERTO REGENCY: (Study at Corn Rice Stall "Yoe Poek" Krapyak Kutogirang) - Wibowo, Nyuherno Aris; Churiyah, Madziatul (Nusantara Economics and Entrepreneurships Journals, 2023)
Human resources are the most important element in an SME ability to achieve goals and develop more broadly. This research aims to learn how to manage human resources to help SME achieve their goals. The research method used is a qualitative empirical study with data collection techniques through interviews and observation. The results of this research show that the strengths of SME are having loyal employees who develop human resources and have a sense of family; the weaknesses are the lack of clear career paths and job desks; the opportunity for employees to come from their own family and the surrounding community; and the threat is the lack of technology mastered by employees and succession. businesses that don't yet exist